Kinematic Decoupling Analysis and Design of a Biomimetic Robotic Elbow Joint - Bingyan Cui; Liwen Chen; Yongtao Xie; Zhijun Wang (Applied Bionics and Biomechanics)
The research of a biomimetic robotic manipulator is based on the flexible characteristics of the human upper limb joint, and a biomimetic robotic elbow joint plays a very significant role in the kinematic control of the biomimetic robotic manipulator. Most robotic elbow joints encountered today have a common disadvantage of bad neutrality, low rotational capability, and poor biomimetics. To overcome some difficulties, this paper presents a novel biomimetic robotic elbow joint. The structural model of the elbow joint is described, and the position equation is solved. Secondly, the kinematic equation of the elbow joint is established, the kinematic decoupling performance evaluation index of the elbow joint is defined, the kinematic decoupling characteristics of the elbow joint are analyzed, and the kinematic decoupling performance map in the workspace is drawn. Thirdly, using the spatial model theory, the structural parameters of the elbow joint are optimized, the structural parameters are selected by the Monte Carlo method, and the novel biomimetic robotic elbow joint is designed. The analysis results showing the kinematic decoupling performance of the elbow joint are symmetrical and the kinematic decoupling performance decreases with the increase of the angle, and there is a good kinematic decoupling in the workspace of about 35% in the vicinity of the initial position. When the structural parameters of the elbow joint are Re1=90 mm, Re2=70 mm, and Re3=30 mm, the elbow joint has a very good kinematic decoupling. This paper can lay a foundation for further analysis and research of the biomimetic robotic elbow joint.